2016
DOI: 10.1523/jneurosci.3274-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Modulation Alleviates Axonal Damage and Cognitive Decline after Rodent Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a major cause of death and disability worldwide. It produces diffuse axonal injury (DAI), which contributes to cognitive impairment, but effective disease-modifying treatment strategies are missing. We have recently developed a rat model of closed skull TBI that reproduces human TBI consequences, including DAI and clinical sequelae such as memory impairment. Here, we investigated whether sleep modulation after trauma has an impact on DAI and memory outcome. We assessed cognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 42 publications
2
45
1
Order By: Relevance
“…It has also been reported that TBI can contribute to nigrostriatal damage (33). Cognitive deficits have also been observed in a model of diffuse axonal injury (34), and blast injury (11). Herein, we utilized the EPM to evaluate aberrant behaviors associated with blast injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that TBI can contribute to nigrostriatal damage (33). Cognitive deficits have also been observed in a model of diffuse axonal injury (34), and blast injury (11). Herein, we utilized the EPM to evaluate aberrant behaviors associated with blast injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent evidence suggests that sleep deprivation for shorter periods may be neuroprotective. Indeed, several studies in focal and global cerebral ischemia [59,61,[65][66][67], cardiac arrest [60] or TBI [64,68,69] murine models have documented that both TSD [59,61,[64][65][66]69] and REMSD [60,64,67] have neuroprotective effects, whether they are applied before the insult [59-61, 65, 66] or after it [64,67,69] as summarized in Table 1. However, some studies indicate that sleep deprivation for short periods had no effect [68] or, its effect was deleterious [62,63] (see Table 1).…”
Section: Neuroprotection and Sleepmentioning
confidence: 99%
“…Holtzman’s group is generating further data which suggests a positive feedback cycle of sleep disruption that could accelerate neurodegeneration during AD [46,53]. On the positive side, sleep induction decreased axonal injury in a rat model of traumatic brain injury [54], and sleep may more generally reduce AD-related neuropathology [55]. …”
Section: Links Between Short Sleep Evolution and Admentioning
confidence: 99%